GÊNERO E VIVÊNCIA COTIDIANA NA INSTITUIÇÃO DO ESPAÇO DA PRODUÇÃO CIENTÍFICA GEOGRÁFICA PARANA - Pinto, Vagner André Morais (2017)
The aim of this research is to comprehend how gender sets the geographical scientific production profile in the academics spaces from Paraná State. Sundry methodological procedures were used aiming to confer intelligibility to the studied phenomenon. At first, it was organized a database of scientific articles from 90 online journals of the geographical area, classified by the Qualis System of CAPES in all the qualifiers strata of the 2013-2015 triennium. Another survey was carried about teachers and their intellectual production through of the digital platforms Lattes, Sucupira, Google Scholar and sites of the Graduate Programs in Geography from Paraná State. Finally, were made questions adapted from the model of the Instituto Brasileiro de Geografia e Estatística (IBGE) for the Pesquisa Piloto de Uso do Tempo and complemented by open questions. Were interviewed twenty researchers (ten women and ten men) in the Graduate Programs in Geography from Paraná State, and these interviews were systematized using a methodology proposed by Silva & Silva (2016). This research makes it possible to affirm that there is a difference of productivity between women and men in the scientific production of Paraná. Women represents 41.13% of the total published articles in the period from 1983 to 2013. Besides, women publishs little quantity in magazines with better qualification according to Qualis criteria. They represent only 15.25% of the scientific publications classified as A1 and 36.03% as A2. The woman with the highest productivity occupies only ranks seventh among the researchers with the highest number of articles published. The impact of male theories is strong, with men corresponding to 3 of the 4 scientists with the highest citation index in the geographic field. Therefore, the structure of scientific production has a gender component. However, the majority of teachers do not agree that gender is an element that influences their academic production and they consider academic space as a neuter and universally egalitarian. Although, as scientific production is a product with time demand for work, in the last decades, this has permeated the private space, there is an impact on the feminine production in consequence of social gendered demands in the domestic space, which differs from men's experience. Thus, the dichotomist geographical imagination between the academic space and the domestic space masks the elements of gender that set the conditions of scientific production.